A COLLECTION OF TICKS (IXODIDAE) FROM SULAWESI UTARA, INDONESIA - L.A. DURDEN (SEAMEO BIOTROP, 1989)
Ixodid ticks were collected from seven species of endemic murid rodents and from vegetation in Sulawesi Utara, Indonesia. Adult ticks belonging to the species, Amblyomma babirussae, A. cyprium and Dermacentor (Indocentor) steini were taken from the vegetation. Immature ticks assignable to the genera, Haemaphysalis, Amblyomma and Ixodes infested the murids with Parauromys dominator and Maxomys musschenbroekii being the two most heavily tick-infested host species. The data are compared to other tick records from Sulawesi.